Effect of Coffee on Pulse Rate Rise - Henim, Audy Aprilia; Samodra, Y. Touvan Juni; Roldan, Patrick John B. (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
The purpose of this study was to determine the effect of coffee on pulse rate. In this research method using experimental methods, the sample is Sports Coaching Education Students Class of 2021 totaling 16 (sixteen) people consisting of 5 (five) women and 11 (eleven) men which was held on May 29, 2023 at 15:30 WIB in the Sports Coaching Education Student Association room (HIMA PKO).  It is known that the comparison of 60 pulse beats per second in students who drink hot coffee and cold coffee measures it in a standing position. The coffee used is ground village coffee with a dose of 1 teaspoon without sugar, using a dose of 220 ml of water, where there are 8 (eight) students drinking coffee using hot water and 8 (eight) students drinking coffee using cold water / ice water. The results using descriptive analysis and inferential analysis using data from IBM SPSS Statistics 22, the pulse rate of drinking hot coffee scored from the lowest was 60 pulse/second and the highest was 116 pulse/second, while the pulse rate of drinking cold coffee had the lowest pulse rate with a score of 63 pulse/second and the highest score was 100 pulse/second. So it can be concluded that drinking hot coffee makes the pulse rate increase the same as drinking cold coffee.